Dose evaluations of organs at risk and predictions of gastrointestinal toxicity after re-irradiation with stereotactic body radiation therapy for pancreatic cancer by deformable image registration - Cao, Yangsen; Zhu, Xiaofei; Yu, Chunshan; Jiang, Lingong; Sun, Yongjian; Guo, Xueling; Zhang, Huojun (Frontiers in Oncology, 2023)
Purpose Re-irradiation of locally recurrent pancreatic cancer may be an optimal choice as a local ablative therapy. However, dose constraints of organs at risk (OARs) predictive of severe toxicity remain unknown. Therefore, we aim to calculate and identify accumulated dose distributions of OARs correlating with severe adverse effects and determine possible dose constraints regarding re-irradiation. Methods Patients receiving two courses of stereotactic body radiation therapy (SBRT) for the same irradiated regions (the primary tumors) due to local recurrence were included. All doses of the first and second plans were recalculated to an equivalent dose of 2 Gy per fraction (EQD2). Deformable image registration with the workflow “Dose Accumulation-Deformable” of the MIM® System (version: 6.6.8) was performed for dose summations. Dose–volume parameters predictive of grade 2 or more toxicities were identified, and the receiver operating characteristic (ROC) curve was used to determine optimal thresholds of dose constraints. Results Forty patients were included in the analysis. Only the V10 of the stomach [hazard ratio (HR): 1.02 (95% CI:1.00–1.04), P = 0.035] and Dmean of the intestine [HR: 1.78 (95% CI: 1.00–3.18), P = 0.049] correlated with grade 2 or more gastrointestinal toxicity. Hence, the equation of probability of such toxicity was P=11+e−(−4.155+0.579Dmean of the intestine+0.021V10 of the stomach) Additionally, the area under the ROC curve and threshold of dose constraints of V10 of the stomach and Dmean of the intestine were 0.779 and 77.575 cc, 0.769 and 4.22 Gy3 (α/β = 3), respectively. The area under the ROC curve of the equation was 0.821. Conclusion The V10 of the stomach and Dmean of the intestine may be vital parameters to predict grade 2 or more gastrointestinal toxicity, of which the threshold of dose constraints may be beneficial for the practice of re-irradiation of locally relapsed pancreatic cancer.